The Mobile Commerce Prospects: A Strategic Analysis of Opportunities in the Banking Sector - Tiwari, Rajnish (Hamburg University Press, 2007)
Mobile Commerce has gained increasing acceptance amongst various sections of the society in previous years. The reasons for its growth can be traced back to technological and demographical developments that have influenced many aspects of the socio-cultural behaviour in today's world. The need (and/or wish) for mobility seems to be the driving force behind Mobile Commerce. The launch of UMTS technology has provided Mobile Commerce with the necessary verve.Mobile Banking presents an opportunity for banks to retain their existing, technology-savvy customer base by offering value-added, innovative services and to attract new customers from corresponding sections of the society. The customer survey provides evidence that such sections in the meanwhile include the affluent and financially relevant groups of the society in Germany. The time seems to be ripe to convert this non-negligible customer interest into business-driving customer demand. A proactive attitude on the part of the banks seems to be therefore recommendable.Many banks in Germany have come to regard Mobile Banking as a necessary tool for thwarting negative differentiation vis-à-vis rivals and to foster/retain an innovative image. This self-reinforcing dynamism is expected to gain currency in near-future so that Mobile Banking services could soon advance to a standard product - on the lines of Online Banking - offered by more or less each and every bank.